JUMPA Vol.4 No.2, Juni 2017 PENGARUH KEPUASAN KERJA KARYAWAN DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PT PLN (PERSERO) DISTRIBUSI JAKARTA RAYA DAN TANGERANG KANTOR DISTRIBUSI: PENGARUH KEPUASAN KERJA KARYAWAN DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PT PLN (PERSERO) DISTRIBUSI JAKARTA RAYA DAN TANGERANG KANTOR DISTRIBUSI - Eka Sulistianingsih Sekolah Tinggi Ilmu Ekonomi Y.A.I; Alex Zami Sekolah Tinggi Ilmu Ekonomi Y.A.I (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2017)
In this thesis investigated is the effect of job satisfaction and organizational culture on Organizational Citizenship Behavior (OCB) on employees of PT PLN (Persero) Distribution Jakarta Raya and Tangerang Distribution Office. The independent variable is job satisfaction (X1) and organizational culture (X2), while the dependent variable is Organizational Citizenship Behavior (Y). The purpose of this research is to know and analyze the influence of job satisfaction and organizational culture on Organizational Citizenship Behavior on employees of PT PLN (Persero) Distribution Jakarta Raya and Tangerang Distribution Office. In this study the data used is primary data through the distribution of questionnaires. The sample technique is stratified rundom sampling using slovin method with error rate of 5% with sample number of 158 employees of PT PLN (Persero) Distribution Jakarta Raya and Tangerang Distribution Office. The results of this study partially (t test) showed that job satisfaction has a significant positive effect on OCB with the value of Thitung 5.490> Ttabel 1.975 and organizational culture to OCB postive and significant influence Thitung 8,736> Ttabel 1,975 while together (Test F) work and organizational culture towards OCB is positive and significant Fcount 42.902> Ftable 3.05